2010
DOI: 10.1001/archoto.2010.191
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Robotic Surgery for Advanced Oropharyngeal Carcinoma

Abstract: This novel transoral robotic surgery treatment regimen offers disease control, survival, and safety commensurate with standard treatments and an unexpected beneficial outcome of gastrostomy dependency rates that are markedly lower than those reported with standard nonsurgical therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
294
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 295 publications
(316 citation statements)
references
References 25 publications
(47 reference statements)
14
294
2
Order By: Relevance
“…To date, such limited approaches have been shown to provide good oncologic and functional results when performed in selected patients and by experienced surgeons 17. Nevertheless, the advantages of transoral robotic surgery for enhancing the surgical field visualization in oropharyngeal tumors and for improving the postoperative outcomes as compared to open approaches have been confirmed by numerous authors since the first descriptions by Weinstein and O'Malley 1, 2, 3, 4, 18, 19, 20. To date, a retropharyngeal ICA has, however, been considered to be a contraindication for TORS due to the risk of a catastrophic vascular injury 10, 21.…”
Section: Discussionmentioning
confidence: 99%
“…To date, such limited approaches have been shown to provide good oncologic and functional results when performed in selected patients and by experienced surgeons 17. Nevertheless, the advantages of transoral robotic surgery for enhancing the surgical field visualization in oropharyngeal tumors and for improving the postoperative outcomes as compared to open approaches have been confirmed by numerous authors since the first descriptions by Weinstein and O'Malley 1, 2, 3, 4, 18, 19, 20. To date, a retropharyngeal ICA has, however, been considered to be a contraindication for TORS due to the risk of a catastrophic vascular injury 10, 21.…”
Section: Discussionmentioning
confidence: 99%
“…Weinstein et al at The University of Pennsylvania [24] reported their outcomes with TORS citing an average follow-up of 26 months. In this study, there were 47 patients with oropharynx cancer staged III and IV.…”
Section: Surgical Options For Treatment Of Opsccmentioning
confidence: 99%
“…The oncologic outcomes from TORS surgery for oropharyngeal cancer (OPC) are slowly emerging, and early outcomes seem promising [24][25][26][27]. In the studies to date, local failure rates vary between 0 and 3 %, with median follow-up rates ranging from 18 to 24 months [24][25][26][27].…”
Section: Surgical Options For Treatment Of Opsccmentioning
confidence: 99%
See 1 more Smart Citation
“…TORS procedures have been described to manage pathologies at numerous anatomic sites from the glottis and hypopharynx to the nasopharynx and skull base [4][5][6]. The most commonly reported use of TORS for malignant disease, however, has been for oropharyngeal cancer, particularly tongue base or tonsillar cancer [3,7,8]. This paper presents the contraindications for TORS oropharyngeal cancer resection as developed and performed at the University of Pennsylvania.…”
mentioning
confidence: 99%